2020
DOI: 10.4103/psychiatry.indianjpsychiatry_333_20
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, practice, behavior, and mental health impact of COVID-19 on doctors

Abstract: Background: COVID-19, like every other pandemic, has imposed an unprecedented threat to doctors' physical and mental health. Literature in this area is sparse. The present study has been done to explore the knowledge, attitude, and behavior of doctors regarding this pandemic and how it influences their depression, anxiety, and stress level. Materials and Methods: This online survey has been done for 10 days. Data were collected on background characteristics, knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 11 publications
7
95
0
1
Order By: Relevance
“…They may be exposed to positive patients (without knowing beforehand) and thus must refer them to a higher medical facility, whereas in other health care facilities like medical colleges and hospitals, frontline doctors deal with already diagnosed COVID patients with full protection like PPEs. A study in North India showed results of 35% of depressive symptoms and 33% of anxiety symptoms in doctors posted in COVID duty, findings that were similar to ours [14]. A study Um DH et al . in South Korea during the MERS outbreak showed a 26% rate of depression, but the sample size at 64 was quite small [10].…”
Section: Comparison With Previous Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…They may be exposed to positive patients (without knowing beforehand) and thus must refer them to a higher medical facility, whereas in other health care facilities like medical colleges and hospitals, frontline doctors deal with already diagnosed COVID patients with full protection like PPEs. A study in North India showed results of 35% of depressive symptoms and 33% of anxiety symptoms in doctors posted in COVID duty, findings that were similar to ours [14]. A study Um DH et al . in South Korea during the MERS outbreak showed a 26% rate of depression, but the sample size at 64 was quite small [10].…”
Section: Comparison With Previous Studiessupporting
confidence: 87%
“…The uncertainty posed by the coronavirus has placed an extra burden on health professionals who may have suffered from anxiety and OCD in the past [13]. A study by conducted by Seshadri Sekar Chatterjee et al in West Bengal (North India) showed 34.9% of the doctors were depressed and 39.5% reported anxiety [14]. Considering the geographical variation, dense population, multi-strata health care structure, and rising COVID cases in South India, we have a reason to speculate that the burden on the frontline doctors is high and that their psychological condition may also be affected during COVID-19 outbreak.…”
Section: Covid and Healthcare Workersmentioning
confidence: 99%
“…Twenty-nine studies were of good quality [16][17][18][19][24][25][26][27][28]31,34,39,41,42,44,46,53,54,57,[59][60][61]63,64,66,68,71,79,80] (score range 7-9) and thirty-six studies were of medium quality [6,20,21,23,27,29,30,32,33,[35][36][37][38]43,45,[47][48][49][50][51][52]55,56,…”
Section: Study Qualitymentioning
confidence: 99%
“…Although, since the outbreak of the COVID-19 pandemic, many researchers have evaluated the mental health issues among the HCWs (Chatterjee et al 2020;Lai et al 2020;Ni et al 2020), there is no systemic study involving the police personnel. Keeping all these in mind, and considering the police work to be physically, emotionally, and mentally taxing, taking appropriate steps to mitigate psychological support to police staff is highly essential.…”
mentioning
confidence: 99%